Penerapan Pendekatan Saintifik dalam Mewujudkan Pembelajaran Abad 21 di Sekolah Dasar - Yantoro; Anissa, Anissa Fitrah (Jurnal PGSD, 2022)
Learning is a process or effort made by each individual to achieve behavior change, either in the form of knowledge, skills, attitudes, positive values, and experiences from various sources studied. Therefore, to help students acquire this knowledge, a learning approach that meets the requirements of the current curriculum is needed: a scientific approach.. The purpose of this study is to describe and describe the phenomena that occur when the application of a scientific approach in realizing 21st century learning. The method used in this study is qualitative with a phenomenological type of research with the research subject of fourth grade teachers at SD Negeri 111/I Muara Bulian Tahun Lesson 2021/2022. The data obtained are observations, interviews, and documentation which are then analyzed through the stages of data reduction, data presentation and conclusion drawing. The results showed that the application of the scientific approach in realizing 21st century learning in grade IV SDN 111/I Muara Bulian was by implementing the steps of the scientific approach activity known as 5M: Observing, Questioning, Trying, reasoning, and communicating and integrating it with 21st century skills.